PENDAMPINGAN PERHITUNGAN HARGA POKOK PRODUKSI PADA USAHA ADELIA KONVEKSI DI TAMBAKBAYA - Maria Ulpah; Rudiyanto; Ela Widasari; Paniran; Siti Mudawanah; Nurhaini (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2020)
Financial Reports are records of a company’s financial information in an accounting period that can be used to describe the company’s performance. In this Community Service Activity, the author provided assistance to the waste paper trading company at Kp. Cemplang Javilan, namely helping to prepare financial reports and providing information regarding financial reports. The method used in the process of preparing financial reports is using the cash basis method which describes financial positions, the author records and classifies bookkeeping evidence, recorded in the general journal and ledger and summarized in a trial balance so that it is reported in the financial report which includes opening trial balance, profit and loss statement, capital changes report and final balance sheet. From the results of the activities the author was able to apply the preparation of financial reports to PD. Paper waste in Kp. Cemplang Jawilan on October 31 to November 30 which can be used to describe the company’s performance. Conclusion, that the financial reports on PD. Limbah Kertas have good company performance. The target given for the progress of Paper Waste requires recording documents when transactions occur, such as sales notes and purchase notes which must be used by companies to anticipate losses that will arise, as well as using more detailed transaction evidence with the aim of improving the condition of the business being run. can be seen how far a company has progressed.